2019
DOI: 10.3390/jcm8111920
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience of Olaparib Maintenance in High-Grade Serous Recurrent Ovarian Cancer Patients with BRCA1/2 Mutation: A Korean Multicenter Study

Abstract: Background: Olaparib maintenance therapy has shown efficacy and tolerability in patients with platinum-sensitive, high-grade serous recurrent ovarian cancer (HSROC) with BRCA1/2 mutation (BRCAm). Our aim was to present real-world experience with olaparib in Korea. Method: We included HSROC patients with BRCAm treated with olaparib maintenance at four institutions in Korea between 2016 and 2018. Medical records were reviewed for clinico-pathologic characteristics, objective response, survival outcomes, and safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
5
3
0
Order By: Relevance
“…The percentage of grade 3–4 hematological AEs, dose reduction (15.3%) and treatment discontinuation (4.2%) in the olaparib maintenance therapy group in our study was very similar to that of different studies ( 4 , 9 , 10 , 26 ). The rates of grade 3–4 hematological AEs, dose reduction (23.5%), dose interruption (23.5%) and treatment discontinuation in patients receiving niraparib were generally lower than those reported in the phase 3 NORA trial ( 7 ), and were comparable to those observed in a real-world study in China ( 27 ).…”
Section: Discussionsupporting
confidence: 88%
“…The percentage of grade 3–4 hematological AEs, dose reduction (15.3%) and treatment discontinuation (4.2%) in the olaparib maintenance therapy group in our study was very similar to that of different studies ( 4 , 9 , 10 , 26 ). The rates of grade 3–4 hematological AEs, dose reduction (23.5%), dose interruption (23.5%) and treatment discontinuation in patients receiving niraparib were generally lower than those reported in the phase 3 NORA trial ( 7 ), and were comparable to those observed in a real-world study in China ( 27 ).…”
Section: Discussionsupporting
confidence: 88%
“…Somewhat larger number of patients whose therapy with olaparib was discontinued because of adverse events in SOLO2 (11%) was already plausibly explained with the relatively longer follow-up (21 months) [3]. Percentage of patients whose olaparib dose was reduced to control the adverse events has been very similar across different studies as well, ranging from 14% in Swedish registry real-world study [19], over 21%, 23%, 25%, and 26% in Italian study [14], Study 19 [2], SOLO2 [3], and our study, respectively, to 36% in Korean study [17]. It seems that the incidence of adverse events is somewhat higher in randomized controlled trials (35% and 36% in Study 19 and SOLO2, respectively) than in real-world data studies (17% in our study and 17% in Chinese study [20]).…”
Section: Discussionsupporting
confidence: 67%
“…Tablets instead of capsules are probably part of the explanation for markedly longer progression-free survival in SOLO2 [3] and our study compared to Study 19 (11.2 months in patients with BRCA 1-2 mutation) [13]. Progression-free survival in the Italian study was almost the same as in the real-world data study performed in Korea in 2016-2018 [17]. Our previous explanation for somewhat shorter progression-free survival in the case of Italian study which postulated the effect of 16% of patients with no objective response to the previous chemotherapy does not hold for the Korean study as they enrolled only the patients with complete or partial response to the last platinum-based treatment before initiation of olaparib, as we and SOLO2 did.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In terms of effectiveness, the OLA users in the current study showed better PFS (median, 23.8 vs. 19.1 vs. 14.6 months), compared to those in SOLO2 [ 11 ] and a previous real-world Korean study [ 17 ]. This may be because our study only included patients who relapsed for the first time, whereas SOLO2 also included patients with multiple recurrences.…”
Section: Discussionmentioning
confidence: 56%